APLIKASI MODEL PEMBELAJARAN BERBASIS MASALAH PADA MATA KULIAH MANAJEMEN DI BIDANG DESAIN INTERIOR - Dwi Prasetya, Rahmawan (Lintas Ruang: Jurnal Pengetahuan dan Perancangan Desain Interior, 2008)
Thirty students of interior design study program Institut Seni Indonesia (Indonesia Institut of Art) Yogyakarta were participated in a study that investigate application of Problem Based Learning Model on 1st Management subject matter (about organization). The result showed that 83.3%participants interest to 1st Management that they didn't like before. As many as 79.2% participants felt that Problem Based Learning Model ease to learn to the subject matter. It is concluded that they more like this model than classical method common did.Keywords: problembased learning, management, organization, interior design